ANALISIS TINGKAT KEPUASAN ANGGOTA ATAS KUALITAS PELAYANAN KOPERASI KARYAWAN INTI NILO SEJAHTERA DESA KEMANG KECAMATAN PANGAKALAN KURAS KABUPATEN PELALAWAN - Nia Riska Kurnia; Suarman Suarman; R M Riadi R M Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study was conducted aiming to determine the level of member’s satisfaction at Employee Corporation of inti Nilo Sejahtera in Kemang Village, Pangkalan Kuras Subdistrict, Pelalawan Regency. In addition, this study was also conducted to examine the effect of service quality toward member satisfaction at Employee Corporation of inti Nilo Sejahtera. The samples of this research were 81 people; those are determined by random sampling. The instrument used was a questionnaire. The descriptive statistic and correlation analysis applyied as data analyzed. The results of the study revealed that the level of member’s satisfaction of Employee Corporation of Inti Nilo Sejahtera categorized as low level, the service quality of Employee Corporation of Inti Nilo Sejahtera categorized as low level. Based on linear regression analysis, it is known that the significant effect between the levels of satisfaction toward service quality was 37.7%, while the other 62.3% was influenced by other variables not examined in this study.Key Words: Members’ satisfaction, Service quality